A Possible Prebiotic Formation of Ammonia from Dinitrogen on Iron Sulfide Surfaces - Dörr, Mark; Käßbohrer, Johannes; Grunert, Renate; Kreisel, Günter; Brand, Willi A.; Werner, Roland A.; Geilmann, Heike; Apfel, Christina; Robl, Christian; Weigand, Wolfgang (Angewandte Chemie International Edition, 2003)
Teaching an old dog a new fix: Nitrogen fixation under mild conditions is still one of the most challenging tasks in chemistry. A method for the synthesis of ammonia from molecular nitrogen using hydrogen sulfide as a reductant and freshly precipitated iron sulfide as a mediator is described. The reaction (see scheme) may be a primordial inorganic ancestor of the enzyme nitrogenase.